The Effect of E-Satisfaction on E-Loyalty through Trust in E-Ticketing on Traveloka in Surabaya - Djukuw, Gery; Tarigan, Zeplin Jiwa Husada (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2024)
This research aims to determine the effect of e-satisfaction on e-loyalty through trust in e-ticketing on Traveloka. The population in this research is Surabaya people who are over 18 years old and use credit cards to make transactions on Traveloka. The number of samples I took was 122 respondents. Data analysis using PLS. The variables in this research are e-loyalty as an endogenous variable and e-satisfaction and trust as exogenous variables. The results of data analysis show that e-satisfaction has a significant and positive effect on e-loyalty through trust in e-ticketing on Traveloka.